Existence of three weak solutions for a perturbed anisotropic discrete Dirichlet problem. Issue 3 (17th February 2019) - Heidarkhani, Shapour; Afrouzi, Ghasem A.; Imbesi, Maurizio; Moradi, Shahin
ABSTRACT: In this paper, we study the existence of at least three distinct solutions for a perturbed anisotropic discrete Dirichlet problem. Our approach is based on recent variational methods for smooth functionals defined on reflexive Banach spaces. Some examples are presented to demonstrate the application of our main results.